2022
DOI: 10.3847/1538-4357/ac74b3
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Estimate of the Half-life for the Radioactive 134Cs and 135Cs in Astrophysical Scenarios

Abstract: We analyze the 55 134 Cs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However the rate of 134 Cs decay estimated from [1] seems currently unsatisfactory [20], as it inhibits the proper reproduction of the two s-only isotopes 134 Ba, 136 Ba in suitable proportions. In particular, in [5] one needs to assume that the temperature dependence of the decay rate is less steep by around a factor of 8 (as modelled in [21]) to level the production of 134 Ba and 136 Ba. Hence, in-plasma measurements could shed light on the role played by the ionization state affecting the β−decay and a simulated virtual experiment was carried out to assess the feasibility and sensitivity of the PANDORA setup and experimental approach to be adopted.…”
Section: Virtual Experimental Run For the Physics Case Of The 134 Cs ...mentioning
confidence: 99%
“…However the rate of 134 Cs decay estimated from [1] seems currently unsatisfactory [20], as it inhibits the proper reproduction of the two s-only isotopes 134 Ba, 136 Ba in suitable proportions. In particular, in [5] one needs to assume that the temperature dependence of the decay rate is less steep by around a factor of 8 (as modelled in [21]) to level the production of 134 Ba and 136 Ba. Hence, in-plasma measurements could shed light on the role played by the ionization state affecting the β−decay and a simulated virtual experiment was carried out to assess the feasibility and sensitivity of the PANDORA setup and experimental approach to be adopted.…”
Section: Virtual Experimental Run For the Physics Case Of The 134 Cs ...mentioning
confidence: 99%
“…In particular, the mainstream (MS) ones, which account for about 90% of all SiC grains, are believed to have originated from carbon AGB stars and show their nucleosynthetic signature [22]. Therefore, isotope ratios of heavy elements measured in MS SiC grains are commonly used to study the s-process occurring in AGB stars and provide constraints on AGB stellar models [23][24][25][26]. Most of the presolar MS SiC grains have been shown to originate from AGB stars with M ∼ 2 M ⊙ and close-to-solar metallicity [27,28].…”
Section: Stellar Magnetic Models and Observationsmentioning
confidence: 99%
“…In these objects, the main neutron source is the 13 C(α, n) 16 O reaction [3,4], while the 22 Ne(α, n) 25 Mg reaction is only marginally activated during the TPs [5]. For the 13 C(α, n) 16 O reaction to effectively operate, some 13 C must be present in the He-rich zone located below the H-rich convective envelope.…”
Section: Introductionmentioning
confidence: 99%
“…However to reproduce the galactic abundances of the 2 s-only nucleus 135 Ba and 136 Ba the temperature dependence of the decay rate for 134 Cs has to be assumed about 8 times less steep than suggested by [17] or by changing upward the cross section of 134 Cs by more than a factor of two [7] . Recently, thanks to an approach based on the solution of the Dirac-Hartree Fock equations, Taioli et al (2022) [20] found the temperature dependence of the 134 Cs and the 135 Cs β−decay rates to smaller than so far assumed. In particular, the half-lives of 134 Cs estimated by the authors is longer than the one by [17] by a factor ranging from 2.5 (near 8-10 keV) to more than 30 (at 30 keV).…”
Section: Light−s Vs Heavy−smentioning
confidence: 99%